Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1083/jcb.201004030
|View full text |Cite
|
Sign up to set email alerts
|

The differential interaction of snRNPs with pre-mRNA reveals splicing kinetics in living cells

Abstract: GFP-tagged snRNP components reveal the dynamics and rate for spliceosome assembly in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
98
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 62 publications
(98 reference statements)
11
98
0
Order By: Relevance
“…[6][7][8] In vivo splicing is achieved within tens of seconds suggesting most introns are spliced out while RNA is still attached to Pol ll and the DNA template. [9][10][11] Consistent with this data, splicing factors have been shown to be recruited to the site of pre-mRNA synthesis and bind the nascent pre-mRNA [12][13][14] and 80% of active spliceosomes are attached to chromatin. 15 This coupling of premRNA splicing and Pol II transcription brings another layer of regulation.…”
Section: Introductionsupporting
confidence: 66%
“…[6][7][8] In vivo splicing is achieved within tens of seconds suggesting most introns are spliced out while RNA is still attached to Pol ll and the DNA template. [9][10][11] Consistent with this data, splicing factors have been shown to be recruited to the site of pre-mRNA synthesis and bind the nascent pre-mRNA [12][13][14] and 80% of active spliceosomes are attached to chromatin. 15 This coupling of premRNA splicing and Pol II transcription brings another layer of regulation.…”
Section: Introductionsupporting
confidence: 66%
“…24 FRAP analysis further revealed that core spliceosomal snRNP proteins have a residence time of 15-30 s in the nucleoplasm, where spliceosomal snRNPs are thought to interact predominantly with pre-mRNA. 25 Based on these results it was suggested that splicing can be accomplished within 30 s, which is significantly more rapid than previously reported. 25 Following the advent of genetically encoded fluorescent protein tags, Belmont and colleagues pioneered a method to image chromatin dynamics in vivo.…”
mentioning
confidence: 67%
“…25 Based on these results it was suggested that splicing can be accomplished within 30 s, which is significantly more rapid than previously reported. 25 Following the advent of genetically encoded fluorescent protein tags, Belmont and colleagues pioneered a method to image chromatin dynamics in vivo. They introduced bacterial lac operator repeats into the genome of yeast and mammalian cells that expressed a GFP-lac repressor fusion protein.…”
mentioning
confidence: 67%
“…We addressed total cellular pre-mRNA by monitoring snRNP dynamics in the nucleoplasm; complementary to this, we used an integrated, inducible transcription unit (E3) containing three exons and two introns of the β-globin gene ( Fig. 4A; Huranova et al 2010;Pabis et al 2010;Brody et al 2011). E3 mRNA contains the MS2 binding site in the 3 ′ UTR, such that active transcription sites can be monitored in living cells with a fluorescently tagged MS2-binding protein.…”
Section: Cbc Promotes U1 and U5 Snrnp Interactions With Pre-mrnamentioning
confidence: 99%